(untitled) (Biological Sciences - PJSIR, 2004)
The electrodimerization mechanism of 4-chloro and 4-bromo- aniline were studied in un-buffered dimethylformamide (DMF) medium. By combined application of conventional and fast voltammetry (100 kV s-1 range), the primary radical cation intermediates, formed by the one electron oxidation of each 4-haloaniline were characterized. The overall reaction path involves a dimerization via an N-C bond formation and de-halogenation at the para position.